Analisis Pelaksanaan Promosi Kesehatan Bagi Karyawan Berisiko Tinggi Penyakit Degeneratif Oleh Health Care Center PT Holcim Indonesia Tbk Cilacap Plant - Laksmi Prihastiwi (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
Based on Medical Check Up (MCU), counted by Framingham score method, held by Health Care Center, 50% employess have a high risk to be infected degenerative diseases, especially diabetes mellitus, hypertension, cardiovascular seen from the measurement of diabetes rate, cholesterol and blood pressure. The goal of the reasearch is to analyze the implementation of health promotion to the employees in high risk degenerativ diseases by Health Care Center PT Holcim Indonesia Tbk Cilacap Plant. The research method that is used quantitative approach with cross sectional reasearch design. Population in this reasearch is the employees of PT Holcim Indonesia Tbk Cilacap Plant that are in high category, seen from MCU result in the amount of 253 persons and 75 respondent, taken as samples, using simple random sampling method. The data sources came from primary and secondary data. Data analysis uses univariat and bivariat analysis with Chi Square test (Significant level 0,05). The result of the research shows that the respondents with a good health promotion that was held well with total amount of 70.7%. Based on the result of Chi Square test, there was a relation between health poster (p value= 0.006) and consultation (p value= 0.002) with the implementation of health promotion for the employees in high risk of degenerative diseases by Health Care Center PT Holcim Indonesia Tbk Cilacap Plant. Meanwhile, for respondents knowledge (p value= 0.072), the role of health workers (p value= 0.098), health education (p value= 0.221), nutrition (p value= 0.720) and physical exercise (p value= 0.272) were not found the relation to the implementation of health promotion for the high risk employees by Health Care Center PT Holcim Indonesia Tbk Cilacap Plant.